2016
DOI: 10.4187/respcare.04493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Exercise-Induced Bronchoconstriction Measured by Standardized Testing in Healthy College Athletes

Abstract: BACKGROUND: Exercise-induced bronchoconstriction (EIB) can lead to long-term respiratory illness and even death. EIB prevalence rates are both high and variable in college athletes. Prevalence rates may be underestimated due to ineffective testing and screening. The purpose of this study was to investigate the prevalence of EIB in college athletes by a standardized EIB test that can be used on many college campuses. In addition, we assessed the usefulness of self-reporting EIB/asthma (1) history, (2) symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
3
17
2
1
Order By: Relevance
“…Their reproduced dyspnea on exertion was associated with various physiological findings. The difference in prevalence of EIB between our study 5 and other SEE THE ORIGINAL STUDY ON PAGE 571 reports of EIB in subjects without asthma, including that of Burnett et al, 1 is probably related to the more stringent criteria we used to define positive EIB. Our study included a higher cutoff value (drop in FEV 1 of Ͼ15% as opposed to Ͼ10%) than the study published in this issue of the Journal.…”
contrasting
confidence: 44%
See 2 more Smart Citations
“…Their reproduced dyspnea on exertion was associated with various physiological findings. The difference in prevalence of EIB between our study 5 and other SEE THE ORIGINAL STUDY ON PAGE 571 reports of EIB in subjects without asthma, including that of Burnett et al, 1 is probably related to the more stringent criteria we used to define positive EIB. Our study included a higher cutoff value (drop in FEV 1 of Ͼ15% as opposed to Ͼ10%) than the study published in this issue of the Journal.…”
contrasting
confidence: 44%
“…Is a Ͼ10% decrease in FEV 1 subsequent to exercise in the absence of clinical dyspnea sufficient for the diagnosis of exercise-induced asthma? The presence of EIB in a child without symptoms of asthma may be, as suggested by Burnett et al, 1 predictive that some minority will eventually develop symptoms of asthma, but most apparently will not. This study as well as most previous studies relating to EIB and asthma symptoms are cross-sectional.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…a large multicenter study in adolescents found that the prevalence of self-reported respiratory symptoms associated with exercise varied greatly, from 6.9 to 37.5% 14 . Similarly, a number of studies in athletes have indicated that the prevalence of self-reported exercise-induced respiratory symptoms ranged from 11 to 26%, but these figures increased to more than 40% in some sports when an exercise challenge documented the eIB 8,9 . Compared with these works, the 7.2% prevalence of eIB found in our study appears to be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that in some high endurance sports, more than 40% of athletes present eIB [8][9][10] , with only a small percentage of these cases linked with a diagnosis of asthma. to our knowledge, in Mexico the prevalence of eIB in athletes is unknown.…”
Section: Introductionmentioning
confidence: 99%